Synthesis of robust hierarchically porous zirconium phosphate monolith for efficient ion adsorption. (8th December 2014) - Zhu, Yang; Shimizu, Taiyo; Kitajima, Takara; Morisato, Kei; Moitra, Nirmalya; Brun, Nicolas; Kiyomura, Tsutomu; Kanamori, Kazuyoshi; Takeda, Kazuyuki; Kurata, Hiroki; Tafu, Masamoto; Nakanishi, Kazuki
Abstract : Hierarchically porous zirconium phosphate monoliths were synthesized and fabricated into a continuous flow setup for toxic metal ion adsorption. Abstract : Hierarchically porous monolithic materials are advantageous as adsorbents, catalysts and catalyst supports due to the better accessibility of reactants to the active sites and the ease of recycle and reuse. Traditional synthetic routes, however, have limitations in designing hierarchical porosity as well as the mechanically stable monolithic shape in inorganic phosphate materials, which are useful as adsorbents and catalysts. We present a low-temperature, one-step liquid phase synthesis of hierarchically porous zirconium phosphate (ZrP) monoliths with tunable compositions (from Zr(HPO4 )2 (Zr : P = 1 : 2) to NaSICON (Na super ionic conductor)-type ZrP (Zr : P = 1 : 1.5)) as well as macropore size (from 0.5 to 5 μm). The as-synthesized ZrP monolith with a high reactive surface area (600 m 2 g −1 ) and relatively high mechanical strength (Young's modulus 320 MPa) was applied to ion adsorption. A simple syringe device inserted tightly with the ZrP monolith as a continuous flow setup was demonstrated to remove various toxic metal ions in aqueous solutions, which shows promising results for water purification.